Chronic Ly49H Receptor Engagement in vivo Decreases NK Cell Response to Stimulation Through ITAM-Dependent and Independent Pathways Both in vitro and in vivo - Key, Phillip N.; Germino, Joe; Yang, Liping; Piersma, Sytse J.; Tripathy, Sandeep K. (Frontiers in Immunology, 2019)
Natural killer (NK) cells play an important role in the innate immune response. The summation of activation and inhibitory signals delivered through cell surface membrane receptors determines NK cell function. However, the continuous engagement of an activating receptor on NK cells appears to render the cells hyporesponsive to stimulation through other unrelated activating receptors. The mechanism by which this takes place remains unclear. Herein we demonstrate that continuous in vivo engagement of the Ly49H receptor with its ligand, m157, results in Ly49H+ NK cells that are hyporesponsive to further stimulation by other ITAM-dependent and independent receptors, while Ly49H- NK cells remain unaffected. The hyporesponsiveness of the NK cell correlates with the degree of Ly49H receptor downmodulation on its cell surface. We observe defects in calcium flux in the hyporesponsive NK cells following stimulation through the NK1.1 receptor. In addition, we observe differences in signaling molecules that play a role in calcium flux, including spleen tyrosine kinase (Syk) at baseline and phosphorylated phospholipase C gamma 2 (p-PLCγ2) at both baseline and following stimulation through NK1.1. We also demonstrate that various ITAM associated activation receptors, including Ly49H, remain associated with their respective adaptor molecules. With regard to in vivo NK cell function, we did not find differences in the formation of metastatic lung lesions following IV injection of B16 melanoma cells. However, we did observe defects in rejection of missing-self targets in vivo. The data suggest that continuous engagement of the Ly49H activating receptor on NK cells results in hyporesponsiveness of the NK cells to all of the ITAM-dependent and independent receptors we analyzed due to altered signaling pathways downstream of the receptor and adaptor molecule.